(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
Detailed biostratigraphic study of mid-Cretaceous Tethys Himalayan pelagic units shed new light on the evolution of the northern India passive continental margin. After a major episode of alkaline magmatism recorded from Zanskar to Nepal in the Early Cretaceous, condensed glauco-phosphorites were deposited during the Rotalipora subticinensis Subzone, and were overlain unconformably by pelagic mudstones during the Rotalipora ticinensis to Rotalipora appenninica Zones (Fatu La Formation in Zanskar and Muding Formation in Nepal). Throughout the Tethys Himalaya drowning of clastic shelves thus occurred with the same modalities and synchronously in Late Albian time. The base of the Chikkim Formation in Zanskar is younger, and overlies palimpsest arenites and reworked glauco-phosphorires deposited during the latest Cenomanian Whiteinella archaeocretacea Zone. Hiatuses several million years long, mainly coeval and similar in duration in the Chikkim and Fatu La Formations, characterize the Cenomanian and the Late Turonian to Campanian sections throughout the Zanskar Range. These hiatuses are ascribed to continuous resuspension of pelagic sediments on the upper slope, caused by the action of strong eastbound oceanic currents. Much higher accumulation rates were recorded in the early-middle Turonian, when deposition occurred at grearer depths below the mudline. Accumulation rates increased greatly in the Maastrichtian, when offshore marls with sparsc phosphate nodules were gradually rcplaced by inner shelf carbonate facies at the close of the Cretaceous. The studied succession shows a mirrorlike repetition of sedimentary facies, interpreted as part of a 65 to 70 my long Cretaceous supersequence. Sedimentary evolution reflected a complex interplay of global and regional phenomena, including the extensional and magmatic episodes leading to thc final fragmentarion of Gondwana-Land and opening of the Indian Ocean, a long-term tendency to eustatic rise, changing paleooceanographic circulation, and oceanic anoxic events.